2021
DOI: 10.1038/s41598-021-95313-y
|View full text |Cite
|
Sign up to set email alerts
|

k-core genes underpin structural features of breast cancer

Abstract: Gene co-expression networks (GCNs) have been developed as relevant analytical tools for the study of the gene expression patterns behind complex phenotypes. Determining the association between structure and function in GCNs is a current challenge in biomedical research. Several structural differences between GCNs of breast cancer and healthy phenotypes have been reported. In a previous study, using co-expression multilayer networks, we have shown that there are abrupt differences in the connectivity patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 68 publications
(86 reference statements)
2
8
0
Order By: Relevance
“…The effect of loss in long range co-expression is consistent with previous works of regulatory networks in breast cancer ( 10 , 12 14 , 33 , 53 ). The block-type structure of the basal subtype matrix suggests the utility of clustering analysis to compare the structural properties of the correlation matrices.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of loss in long range co-expression is consistent with previous works of regulatory networks in breast cancer ( 10 , 12 14 , 33 , 53 ). The block-type structure of the basal subtype matrix suggests the utility of clustering analysis to compare the structural properties of the correlation matrices.…”
Section: Resultssupporting
confidence: 91%
“…In cancer, gene co-expression networks have been used to uncover genes and relationships that may represent crucial elements to determine differences between phenotypes ( 32 ). In particular, in breast cancer and breast cancer molecular subtypes ( 4 ), gene co-expression networks have been useful to identify the phenomenon of loss of long-range co-expression ( 10 , 12 , 14 , 33 ): this is, a property observed in cancer networks in which the most significant gene co-expression relationships occur between genes that belong to the same chromosome, i.e., cis- interactions. Conversely, inter-chromosome ( trans- ) interactions are often weak in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The bias to intra-chromosomal interactions has been previously reported by our group in gene co-expression networks for breast cancer (28,48,(70)(71)(72), lung cancer (31), and also CCRC (32). These results show a clear trend to favor close gene correlations in terms of base pair distance.…”
Section: Mir-217 Is Differentially Expressed In All Sequentially Cont...supporting
confidence: 78%
“…Regarding the enrichment of a chromosome location, chr16p13 is exceptionally significant. Many studies have confirmed that mutations and abnormal expression of the region are highly correlated with breast cancer [22][23][24] . The result of gene enrich in gene ontology(GO) shows the microtubule cytoskeleton involved in mitosis is highly correlated with the development of TNBC, which is highly consistent with the clinical practice and some research 25,26 .…”
Section: Case Study: Transcriptome Of Breast Cancermentioning
confidence: 99%